First report on identification and genomic analysis of a novel porcine circovirus (porcine circovirus 4) in cats - Xu, Tong; Deng, Li-Shuang; Jian, Zhi-Jie; Xu, Lei; Li, Feng-Qin; Lai, Si-Yuan; Ai, Yan-Ru; Zhu, Ling; Xu, Zhi-Wen (Frontiers in Microbiology, 2023)
Porcine circovirus type 4 (PCV4) is an emerging circovirus, which has been detected in domestic pigs across various provinces in China and Korea. In this study, we aimed to investigate whether cats are susceptible to PCV4. For this purpose, we collected 116 cat samples from animal hospitals in Sichuan Province, China, between 2021 and 2022. Using a SYBR Green-based real-time PCR assay, we detected PCV4 in 5 out of the 116 clinical samples, indicating a positive rate of 4.31%(5/116) and confirming the presence of PCV4 in cats from Sichuan Province, China.Moreover, we successfully sequenced and analyzed the complete genome of one PCV4 strain (SCGA-Cat) along with 60 reference sequences deposited in the GenBank database. SCGA-Cat exhibited high nucleotide homology (98.2-99.0%) with PCV4 strains from other species, including dogs, pigs, dairy cows, and fur animals. Notably, the SCGA-Cat strain from cats clustered closely with a PCV4 strain derived from a pig collected in Fujian Province, China. To the best of our knowledge, this study represents the first report on the molecular detection of PCV4 in cats worldwide, which prompted us to understand the genetic diversity and cross-species transmission of the ongoing PCV4 cases. However, further investigations are needed to explore the association between PCV4 infection and clinical syndromes in cats.